Case Report: Challenges of an extremely delayed diagnosis of classic congenital adrenal hyperplasia in a completely virilized 46,XX patient - Casiraghi, Alice; Campi, Irene; Federici, Silvia; Cernigliaro, Franco; Menabò, Soara; Persani, Luca (Frontiers in Endocrinology, 2025)
Classic Congenital Adrenal Hyperplasia (CAH) due to 21-hydroxylase deficiency is typically diagnosed in early life. We report a 46,XX completely virilized 46,XX patient who was diagnosed with classic CAH at the age of 73 years. He was under follow-up for prostate hyperplasia and referred after the finding of giant bilateral adrenal myelolipomas. He presented with hormonal values initially interpreted as suggestive of hypogonadotropic hypogonadism, prompting further biochemical and genetic analysis. Next-generation sequencing identified heterozygous variants in X-linked genes, uncovering a 46,XX difference of sex development (DSD). Then, CYP21A2 molecular analysis revealed compound heterozygosity for two pathogenic variants (p.I173N, p.R357W), confirming simple virilizing CAH. The patient’s reticent attitude contributed to the diagnostic delay. However, this unique case reveals the challenges generated by the paraurethral glands hyperplasia - mimicking a prostate due to prolonged untreated hyperandrogenism - as well as the repeated failure to recognize Müllerian remnants on imaging and the critical issues related to diagnostic communication.